Bulk-fill giomers: effectiveness of cure and cross link density associated with different light curing modes - Jia, Wei Lee; Bao, Hui Chan; Noor Azlin Yahya; Zamri Radzi; Yap, Adrian U-Jin (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigated the influence of light-curing modes on the effectiveness of cure and cross-link density of restorative (Beautifil Bulk-fill Restorative [BR]) and flowable (Beautifil Bulk-fill Flowable [BF]) giomers. The giomers were placed in black opaque acrylic moulds with cylindrical recesses of 5 mm diameter and 4 mm height, and photo-polymerized with a LED light (Bluephase N) using the following modes: High power (HP) 1200 mW/cm2 (10 s); Low power (LP) 650 mW/cm2 (18.5 s); Soft start (SS) 650 mW/cm2 (5 s) followed by 1200 mW/cm2 (10 s). The polymerized specimens were stored at 37 °C for 24 h, after which the top and bottom surfaces of the samples were subjected to microhardness testing to assess the effectiveness of cure. The specimens were then conditioned in 75% ethanol-water solution at 37 °C for 24 h and subjected to post-conditioning microhardness testing to determine cross-link density. Mean bottom-to-top hardness ratios and the softening effect (ΔKHN) with ethanol-water solution were computed. Data were analyzed using one-way ANOVA/post-hoc Bonferroni’s test and independent samples T-test (α=0.05). The influence of curing modes on the effectiveness of cure and cross-link density were material dependent. Mean pre-conditioning hardness ratios varied from 40.67 to 50.69 for BR and 59.98 to 67.89 for BF with the different curing modes. The most effective cure was achieved with LP and SS for BR and BF, respectively. The lowest cross-link density was observed with LP for both giomers. In conclusion, the effectiveness of cure and cross-link density of bulk-fill giomers are more influenced by the material type than light-curing modes applied.